SELENIUM ISOTOPE RATIOS AS INDICATORS OF SELENIUM SOURCES AND OXYANION REDUCTION - Johnson T.M.; Herbel M.J.; Bullen T.D.; Zawislanski P.T. (My University, 1999)
Selenium stable isotope ratio measurements should serve as indicators of sources and biogeochemical transformations of Se. We report measurements of Se isotope fractionation during selenate reduction, selenite sorption, oxidation of reduced Se in soils, and Se volatilization by algae and soil samples. These results, combined with previous work with Se isotopes, indicate that reduction of soluble oxyanions is the dominant cause of Se isotope fractionation. Accordingly, Se isotope ratios should be useful as indicators of oxyanion reduction, which can transform mobile species to forms that are less mobile and less bioavailable. Additional investigations of Se isotope fractionation are needed to confirm this preliminary assessment.We have developed a new method for measurement of natural Se isotope ratio variation which requires less than 500 ng Se per analysis and yields ±0.2‰ precision on 80Se/76Se. A double isotope spike technique corrects for isotopic fractionation during sample preparation and mass spectrometry. The small minimum sample size is important, as Se concentrations are often below 1 ppm in solids and 1 μg/L in fluids. The Se purification process is rapid and compatible with various sample matrices, including acidic rock or sediment digests.